FACTORS INFLUENCING BIRTH AND GESTATION PERIOD IN SHARABI CATTLE - I.Said, S.; A.Alrawi , A.; A.Ali , A. (The Iraqi Journal of Veterinary Medicine, 1989)
Birth weight, of 166 Sharabi offspring of 19 sires were analyzed, using a mixed model. Effects of month and year of calving and sex on birth weight and gestation period were significant (p<0.01), least -squares means for birth were 19.24+1.2 kg and weight and gestation period 280.5+0.7 days, respectively. The heritability of the former was 1.04+0.346.